1960
DOI: 10.1139/y60-053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dietary Lysine Deficiency on the Concentration of Amino Acids in the Deproteinized Blood Plasma of Chicks

Abstract: A lysine-deficient basal diet, both with and without supplemental lysine added, was fed to groups of Barred Plymouth Iiock cockerels from hatching to 4 weeks of age. .4t this time blood sanlples were taken from the carotid artery and pooled for each group. Twelve amino acids were determined in the deproteinized plasma by microbiological assay. Deproteinized plasma from birds receiving the lysine-deficient diet was lower in lysine content and higher in threonine and tyrosine than that from birds fed the lysine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1962
1962
1977
1977

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…This is in agreement with the results of Gray et al (1960) and by Hewitt (1966), as reported by Lewis (1967).…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with the results of Gray et al (1960) and by Hewitt (1966), as reported by Lewis (1967).…”
Section: Discussionsupporting
confidence: 94%
“…The preparation of the protein-free plasma and the method for the determination of glutamic acid and glutamine have been described in previous papers (Gray et al, 1960;Olsen et ah, 1962). Heparin was used as an anticoagulant.…”
mentioning
confidence: 99%
“…Direct application of this method failed to predict limiting amino acids when the chick was used as a test animal (Smith and Scott, 1965a, b;Dean and Scott, 1966). Difficulty in application of this method with the chick resulted mainly from the considerable elevation of concentrations of lysine and threonine that occur during starvation (Gray et al, 1960). The extent of the elevation in the concentrations of amino acids varies among species (Shao and Hill, 1967;Boomgaardt and Mc-Donald, 1969).…”
Section: Introductionmentioning
confidence: 99%